ФАРҒОНА ВОДИЙСИ ХАЛҚЛАРИДА АНЪАНАВИЙ ДАФН ВА ТАЪЗИЯ МАРОСИМЛАРИ (Этнографик материаллар таҳлили) (Scientific journal of the Fergana State University, 2023)
The article examines the traditional burial and ritual ceremonies of the peoples of Fergana Valley. It provides a comparative analysis of the material on different ethnic groups